Papillomavirus Immune Evasion Strategies Target the Infected Cell and the Local Immune System - Zhou, Chenhao; Tuong, Zewen Kelvin; Frazer, Ian Hector (Frontiers in Oncology, 2019)
Persistent infection with human papillomavirus (HPV) initiates ~5% of all human cancers, and particularly cervical and oropharyngeal cancers. HPV vaccines prevent HPV infection, but do not eliminate existing HPV infections. Papillomaviruses induce hyperproliferation of epithelial cells. In this review we discuss how hyperproliferation renders epithelial cells less sensitive to immune attack, and impacts upon the efficiency of the local immune system. These observations have significance for the design of therapeutic HPV cancer immunotherapies.